Elementy wizualne w kulturze eksperymentu w ujęciu psychologicznym - Poczynok, Julia (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
In the article there is a whole range of the different examples related to the culture of experiment, especially in the context of the interrelations between literature and visual arts, music and photography. The paper touches upon the questions of mediality, intermediality, the relationship between word and picture, as well as sound and movement. The main aim of the article is to demonstrate the phenomenon of interweaving various types of arts worldwide.